Proyecto I+D 10/84 agroenergética : comunidades de matorral - Luis E.; Tárrega R.; Zuazúa T.; Calvo L. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
Three shrubland zones have been studied with the aim of knowledge the regeneration of shrub vegetation community after the impact of several degenerative and drastic processes as rooting up, cutting or fire. Four control plots of about 100 m2 were defined in each of the zones. One of them was left as a witness and the other three received a different treatment. Their structural composition were evaluated before and after.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)